Father-daughter lust: Psychiatric aspects of abusive incest - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2006)
Sexual violation of children has been a long standing problem that has a wide range of impact upon the victim, her/his family, the community where the family lives and our society as a whole. Traumatic incest, in particular, is an abuse of power, a challenge to the child's sense of trust in people and a thief of childhood. This article will explore the intricate issues surrounding the incest relationship between fathers and their child daughters and provide a discussion of current therapeutic interventions. Copyright 2006 American Journal of Forensic Psychiatry.
Keywords: behavior therapy; child sexual abuse; cognitive therapy; daughter; dept.swk; father child relation; human; incest; play therapy; review; sexual behavior; sexual crime; trust; ⛔ No DOI found